ECONOMIC ASPECTS OF LEGAL PROTECTION OF INNOVATIVE BUSINESS - STASOVSKA, Galyna (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article analyzes the economic aspects of legal protection of innovative entrepreneurship. The author of the article substantiates the approach to legal protection of intellectual assets of innovative business and defines the role of the national IP office of intellectual property and innovations of Ukraine, which becomes a professional technopolis with a complex cycle for innovators; created for an integrated service and a new approach to services. In particular, the practices of solving tasks of commercialization of intellectual assets and expansion of commercial relations in innovative entrepreneurship are studied. The author pays special attention to the commercialization of intellectual assets of innovative entrepreneurship, which is determined by the market approach to innovative development and creates conditions for the development of innovations; solves the problems of introducing an intellectual product on international and national markets. Commercialization of intellectual assets is defined as the materialization of ideas, developments and innovations of commercial products of innovative business.The effective use of intellectual assets in innovative entrepreneurship affects the stable functioning of the intellectual property market, which responds to the dynamics of the development of innovations and changes in the legislative framework in the process of improving state regulation. Legal support promotes the protection of intellectual assets in the process of commercialization. Regulatory authorities prescribe legal methods for licensing innovations and implementing innovations in the process of commercializing intellectual assets of innovative entrepreneurship. In Ukraine, innovative entrepreneurship implements legislative norms for creating innovative strategies based on regulatory processes in terms of: 1) licensing and permitting activities regarding the use of intellectual assets; 2) creation of innovative projects for the development of intellectual assets; 3) organization of joint ventures and partnerships taking into account intellectual assets. In order to adjust the regulatory and legal process, it is recommended to use the road map of innovative entrepreneurship, which determines the priorities of the commercialization of intellectual assets at the stages of the strategic plan. The author's recommendations are aimed at using the road map of innovative entrepreneurship, which determines the priorities of the commercialization of intellectual assets at the stages of the strategic plan; improves the procedure for making management decisions and providing information about development prospects and alternatives.
Keywords: innovative development; intellectual assets; innovative entrepreneurship; innovative business; legal protection; commercialization; road map